Kandungan Senyawa Fitokimia dan Aktivias Antioksidan dari Ekstrak Daun Alpukat (Persea americana Mill.) : Narrative Review - Michelle Jovelyna My Angel Pasaribu; Ihsanti Dwi Rahayu; Muhammad Iqbal; Ari Sri Ulandari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Avocado leaves have long been used by Indonesian people as traditional medicine. Many studies have shown that the plant has many active compounds that have the potential to prevent cell damage caused by free radicals. The purpose of this narrative review article is to collect and review references related to the phytochemical compound content and potential antioxidant activity of avocado leaf extract (Persea americana Mill.). The search and review of literature used in writing this article was carried out by searching for reference sources by combining relevant keywords such as